Bor‐Bor‐Dreifachbindung - Lothar Jaenicke (Chemie in unserer Zeit, 2012)
PURPOSE OF REVIEW: Systemic sclerosis (SSc) is a clinically heterogeneous chronic immune-mediated inflammatory disease with the highest mortality rate among all rheumatic diseases. Although current SSc clinical and serological classifications provide valuable prognostic information, predicting disease progression, and therapeutic responses remains challenging. In this context, genomics holds potential to bridge this gap. This review summarizes recent advances in SSc genomics and discusses their potential clinical applications in disease prediction, patient stratification, and therapeutic development. RECENT FINDINGS: Over the past decade, genomic studies, mainly genome-wide association studies (GWAS) and sequencing-based approaches, have expanded our understanding of the genetic architecture of SSc, identifying susceptibility loci and pathways involved in immune dysregulation, vasculopathy, and fibrosis. Several approaches, including polygenic risk scores (PRS) and drug repurposing, have been performed with the potential to translate these results to clinical setting. SUMMARY: Genomic discoveries in SSc are increasingly aiming to move beyond disease susceptibility towards clinically relevant applications. The integration of genomic, molecular, and clinical data may improve risk stratification, enable earlier identification of SSc patients at risk of severe complications, and support the development of personalized therapeutic strategies. Continued efforts in identifying causal variants and deciphering their underlying mechanisms through functional genomics will be essential for a better translation of genetic findings into precision medicine approaches for SSc.